1985
DOI: 10.1007/bf00214621
|View full text |Cite
|
Sign up to set email alerts
|

Retinal neuropeptides in the skates, Raja clavata, R. radiata, R. oscellata (Elasmobranchii)

Abstract: The distribution of immunoreactive neuropeptides was investigated in the retina of three species of skates (Raja clavata, R. radiata, R. oscellata), elasmobranch fish often used in electrophysiological work on the retina. Enkephalins, neuropeptide Y (NPY), substance P and glucagon were found in different types of amacrine cells. All four peptides appeared in cell bodies in the innermost part of the inner nuclear layer. Processes from the cells containing enkephalins were numerous and ramified throughout the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…NPY-IR was detected in dog, dolphin, human, cat and rat GCL. In contrast, several studies have shown that ganglion cells of some species do not present NPY-IR; examples include baboon, pig, guinea pig, skate, rainbow trout, goldfish, killifish (Blank et al, 1997;Bruun et al, 1985Bruun et al, , 1986Kang et al, 2001;Osborne et al, 1985;Subhedar et al, 1996). In goldfish retina, NPY-IR was detected occasionally in a small number of fibers in the optic nerve, suggesting the presence of NPY in ganglion cells axons (Muske et al, 1987).…”
Section: Horizontal Cellsmentioning
confidence: 86%
See 3 more Smart Citations
“…NPY-IR was detected in dog, dolphin, human, cat and rat GCL. In contrast, several studies have shown that ganglion cells of some species do not present NPY-IR; examples include baboon, pig, guinea pig, skate, rainbow trout, goldfish, killifish (Blank et al, 1997;Bruun et al, 1985Bruun et al, , 1986Kang et al, 2001;Osborne et al, 1985;Subhedar et al, 1996). In goldfish retina, NPY-IR was detected occasionally in a small number of fibers in the optic nerve, suggesting the presence of NPY in ganglion cells axons (Muske et al, 1987).…”
Section: Horizontal Cellsmentioning
confidence: 86%
“…In contrast, the distribution of NPY-IR fibers in the skate retina (R. clavata, R. radiate and R. oscellata) is more similar to that in mammals than to other poikilotherms. Amacrine cells with NPY-IR in cell bodies in the INL send their processes mainly to sublamina 1, but also to sublamina 2 of the IPL Often, NPY-IR fibers reach sublamina 3 and, more rarely, the other IPL sublayers (Bruun et al, 1985(Bruun et al, , 1986. In trout retina (S. gardnieri), a network of fine NPY-IR varicose nerve fibers was seen throughout the IPL.…”
Section: In Contrast Npy Stimulates the Release Of [ 3 H]-glycinementioning
confidence: 97%
See 2 more Smart Citations
“…Glucagonlike immunoreactivity (GLI) has also been localized anatomically in the turtle , skate (Bruun, et al, 1985), mouse and rat (Das, et al, 1985), chicken (Tornqvist et al, 1981;Kuwayama et al, 1982) and larval tiger salamander retinas (Yang & Yazulla, 1986;Yang et al, 1991). Radio-immunoassay studies have found higher retinal levels of glucagon in cold blooded vertebrates and birds (10-35 pg mg -1 protein) than mammals (0.04-0.2pgmg 1 protein) (Ekman & * To whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 96%